(untitled) (Plant Tissue Culture and Biotechnology, 2011)
Hot extract of Aulosira fertilissima (cyanobacterium) added in different proportions to MS as a liquid culture media for the in vitro propagation of Bacopa monnieri (L.) Pennell. Maximum numbers of shoots were induced from axillary node in MS media (40 ml) + Aulosira extract (60 ml) and maximum shoot multiplication was observed when Kn (1.0 mg/l) was added in the shoot initiation media (mentioned above). Surprisingly rooting was also found to be best in the same combination of MS + cyanobacterial extract that was used for initiation and multiplication of shoots. On an average within a period of three subcultures (2 - 3 months) the nodal explants generated 400 shoots. Rooted plantlets were successfully transferred to the field, after acclimation in the net house. Key words: Baccopa monnieri, Cyanobacterial extract, Regeneration, Acclimation D.O.I. 10.3329/ptcb.v20i2.6917 Plant Tissue Cult. & Biotech. 20(2): 225-231, 2010 (December)